Analisa Marketing Mix (7p) Dan Perilaku Konsumen Terhadap Keputusan Kuliah Di Universitas X - Hasibuan, Bernard; Cahyaputri, Bunga (Fakultas Ekonomi Universitas Gresik, 2023)
Higher education is an important pillar of education for the progress of the Indonesian nation. The growth in the number of Private Universities (PTS) in Indonesia is increasing, which has led to the intense competition. Conditions during the Covid pandemic that affected the people's economy were also one of the problems with the decline in new students at PTS, including University X. The marketing strategy is an important factor in attracting prospective students. One of them is the Marketing Mix and consumer behavior with the S-O-R (Stimulus-Organism-Response) model. This study aims to determine the effect of marketing mix variables (products, price, place, promotion, people, process, physical environment) and consumer behavior on student decisions in choosing a university. The results showed that the Marketing Mix variables simultaneously influenced prospective students' decision to study at X University. The product, place, people and process variables were variables that had a significant effect while the physical environment, price and promotion variables had no significant effect on individual students' decision to study at X University.